2021
DOI: 10.1177/17446295211030097
|View full text |Cite
|
Sign up to set email alerts
|

The perspective of emerging adults with Down syndrome – On quality of life and well-being

Abstract: This study explored the thoughts of emerging adults with Down syndrome on quality of life and subjective well-being. Eight 22-year-olds participated in interviews. Data was analysed with content analysis. Four themes were revealed: Work based on interest and capability, having an active and social leisure life, a safe place to live and the use of information and communication technology. Two context related patterns were identified showing that quality of life and subjective well-being were related to individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 27 publications
(46 reference statements)
0
19
0
Order By: Relevance
“…A total of 24 studies focused on the personal development of adults with DS. Four self-reported [ 62 , 64 , 65 , 68 ], two parent-proxy reports [ 74 , 76 ] and four studies using both self-and proxy-reported [ 90 , 93 , 95 , 100 ] examined the educational status of adults with DS who had attended mainstream schools and further education colleges. Two studies [ 76 , 90 ] reported that adults with DS were in their late 30s at the time of the study and in school, with 79% reading and/or look through books at least once a week [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 24 studies focused on the personal development of adults with DS. Four self-reported [ 62 , 64 , 65 , 68 ], two parent-proxy reports [ 74 , 76 ] and four studies using both self-and proxy-reported [ 90 , 93 , 95 , 100 ] examined the educational status of adults with DS who had attended mainstream schools and further education colleges. Two studies [ 76 , 90 ] reported that adults with DS were in their late 30s at the time of the study and in school, with 79% reading and/or look through books at least once a week [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies [ 62 , 64 , 65 , 68 , 82 , 84 , 86 , 88 , 95 , 100 ] found that adults with DS demonstrated reading and writing skills, four studies [ 62 , 68 , 84 , 88 ] reported numeracy skills, and four studies [ 62 , 64 , 94 , 95 ] reported on computer skills. Female adults with DS showed a significant difference in literacy and numeracy skills compared to males, while male adults with DS scored slightly higher in concept attainment and money skills [ 88 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main limitation of the study is that the evaluation of QoL relied on a parent-report instrument and that we missed other sources of information, for example self-or teacherreports. However, self-report instruments or interviews used to measure the QoL in individuals with ID, included DS, mainly target adult age (75)(76)(77). Unfortunately, the use of parent/caregiver-report instruments seems to be the only way to explore the QoL in children with moderate or severe ID.…”
Section: High Quality Of Life Is Perceived In Children With Good Anal...mentioning
confidence: 99%
“…However, less is known about how individuals with DS use these foundational skills during social interactions in later childhood and adolescence. This lack of information represents a critical gap in the literature, given the range of individual differences in outcomes related to social development, such as independent living, employment, community participation, and quality of life, that have been reported among adults with DS ( Iarocci et al, 2008 ; Scott et al, 2014 ; Jevne et al, 2022 ; Loveall et al, 2022 ). One major barrier is that few measures of social skills have been established in this population ( Esbensen et al, 2017 ; Schworer et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%